2014
DOI: 10.1089/scd.2013.0152
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Derived Stromal/Stem Cells Induce Functional CD4+CD25+FoxP3+CD127Regulatory T Cells Under Low Oxygen Culture Conditions

Abstract: Human adipose tissue stromal/stem cells (ASCs) are known to induce proliferation of resting T cells under ambient (21%) O 2 conditions; however, ASCs exist physiologically under lower oxygen (5% O 2 ) conditions in adipose tissue. The effects of low oxygen levels on ASC immunomodulation of T cells are unknown. In this study, we show that ASCs stimulated proliferation of naive CD4+ T cells and the percentage of CD25 + T cells was significantly increased under both low and ambient O 2 . Forkhead box P3 (FoxP3) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Despite the extensive use of biomaterials with specific biophysical and biochemical properties and ability to deliver biochemical stimuli to direct differentiation of MSCs, similar approaches have largely been unexplored for directing the immunomodulatory paracrine activity and broader trophic effects of MSCs. Numerous studies have demonstrated that MSC paracrine factor secretion is modulated in response to environmental cues in addition to the local cytokine milieu, including matrix composition, mechanics, and topography , , as well as oxygen tension . Furthermore, environmental stimuli are highly amenable to manipulation via biomaterials to specifically define the microenvironment of stem cells and direct their function .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive use of biomaterials with specific biophysical and biochemical properties and ability to deliver biochemical stimuli to direct differentiation of MSCs, similar approaches have largely been unexplored for directing the immunomodulatory paracrine activity and broader trophic effects of MSCs. Numerous studies have demonstrated that MSC paracrine factor secretion is modulated in response to environmental cues in addition to the local cytokine milieu, including matrix composition, mechanics, and topography , , as well as oxygen tension . Furthermore, environmental stimuli are highly amenable to manipulation via biomaterials to specifically define the microenvironment of stem cells and direct their function .…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β has a central role in maintenance and induction of FoxP3 expression in vitro, activating signaling pathways involving SMADs and NFAT, which bind the TGF‐β sensitive element (enhancer) within the FoxP3 locus [52, 53]. In accordance with this, we demonstrate here that inhibition of TGF‐β signaling was accompanied with a parallel and significant reduction in the frequency of two T‐cell subpopulations, CD4 + CD25 − Foxp3 + and CD4 + CD25 high Foxp3 + , implying that the first may represent a subset of TGF‐β‐dependent Treg precursors.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of MSC transplantation is related to their potency to differentiate into multiple lineages ( 18 ). Their administration has been shown to improve the tissue environment via endocrine/paracrine effects ( 19 , 20 ) and have immunosuppressive effects ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%